Sistem Aplikasi Penjualan dan Penggajian Pada CV. Arabians Kebab Berbasis Web - Sumijan, Sumijan; , Dr. Ir. Bana Handaga, M.T (2016)
Technology applications more rapidly growing moment by moment could change the business world, especially in economics and business enterprises. The development of information technology has changed the people in resolving their work has changed even the aspects of human life such as search and report data quickly and accurately. CV. Arabian's Kebab is an economic business activities and businesses operating in the food field. Since its establishment five years ago, precisely in 2010 up until now have had 10 outlets and seven members of the partnership are spread around Surakarta but in terms of recapitulation data still use the traditional way of record in the ledger and for proof of sale of goods to members partnerships are still using manual paper memorandum written by the recording clerk / cashier, so that the process becomes slow for business owners to see good sales reports daily and monthly and even yearly. Application sales is a way to handle the issue of stock items, sales of goods, purchases of goods and print a variety of reports. Web-based sales application built using the PHP programming language and MySQL database. Sales Application System uses software Notepad ++, XAMPP 1.6.6a. The system is designed using SDLC (System Development Life Cycle). Application of research results in the form of web-based sales and payroll. This application has been successfully applied by the business owner or the admin is by doing some of the input data and print reports. In addition it has also been successfully applied by the operator or registration personnel by doing a few sales and purchases. So with this sales application can be a means for recording the cashier or attendant to the sale, purchase, print reports and lists inventory quickly and accurately as expected.